ANALISIS DAMPAK PEMBANGUNAN PELABUHAN PATIMBAN DI KECAMATAN PUSAKANEGARA TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT SEKITAR - Asep Bambang Iryana (Universitas Jenderal Ahmad Yani, 2018)
Patimban Port, which is located in Patimban Village, Pusakegara District, Subang Regency, West Java Province, is designated as a national strategic project as regulated in Presidential Regulation No.3 of 2016 concerning the Acceleration of Implementation of National Strategic Projects. The implementation of Patimban Port as a national strategic project, according to this Presidential Decree, includes planning, development, operation and exploitation activities, technical guidance and development of port operation management, as well as guidance to ensure shipping safety and the environment. This port development is the Government's strategy to reduce excess capacity at Tanjung Priok Port. Basically, ports have an important role in the development of industry, trade and services and hope that Subang Regency will become a metropolitan industrial city. Data collection techniques, namely: observation, interviews and documentation. The data validity techniques used in the study were source triangulation and method triangulation. The data analysis technique used is qualitative data analysis techniques, namely data collection, data reduction, data presentation and conclusion. Based on the results of the discussion obtained about the Analysis of the Impact of the Development of Patimban Port in Pusakegara District on the Socio-Economic Conditions of the Surrounding Community, there are three points, namely: the impact of socio-economic conditions, the impact of livelihoods and the impact of population mobility. The socio-economic impact of the occurrence of public perceptions of positive and negative changes. A positive change is the location of Patimban Village, which has become more famous than before the port development. A negative change is the development of the Patimban Port where there will be social interaction where there will be many residents who come from outside the region who come as job seekers because later there will be many companies operating in the Patimban Port. Of course this will gradually change the habits of the surrounding community along with the development of Patimban Port. The impact of livelihoods will be the displacement of their former livelihoods as farmers and fishermen, where farmers will have less agricultural land as a result of land acquisition for the benefit of ports and fishermen who are increasingly distant to sea. The impact of population mobility caused by the development of Patimban Port includes three patterns, namely being regulated by the government, their own will and depending on others.